Back Cover: A Novel Metastable Pentavalent Plutonium Solid Phase on the Pathway from Aqueous Plutonium(VI) to PuO2 Nanoparticles (Angew. Chem. Int. Ed. 49/2019). Issue 49 (8th November 2019) - Kvashnina, Kristina O.; Romanchuk, Anna Yu.; Pidchenko, Ivan; Amidani, Lucia; Gerber, Evgeny; Trigub, Alexander; Rossberg, Andre; Weiss, Stephan; Popa, Karin; Walter, Olaf; Caciuffo, Roberto; Scheinost, Andreas C.; et al.
Abstract : A novel pentavalent plutonium solid phase was observed on the pathway from aqueous Pu VI to PuO2 nanoparticles, as reported by K. O. Kvashnina et al. in their Communication on page 17558 ff. This was achieved by combining a high‐energy‐resolution fluorescence detection method at the Pu M4 and L3 edges with electronic‐structure calculations.